A common drug of paracetamol contributes to oral hypersensitivity: A case report - Abnas, Rizqi J.; Marlina, Erni; Usman, Nur A.; Putri, Andi AM.; Israyani, Israyani; Harlina, Harlina (Journal of Case Reports in Dental Medicine, 2025)
Introduction: Paracetamol is the most commonly used analgesic drug in the general population, but it can cause hypersensitivity reactions in certain individuals. This case report describes the diagnosis of erythema multiforme due to hypersensitivity to paracetamol.Case Report: An 11-year-old girl presented to her parents with chief complaints of peeling, bleeding lips, erosive lesions, and pain on the lip commissure. Anamnesis revealed that the complaints had occurred for 5 days. The patient had no history of drug or food allergies. Clinical examination showed red erosion lesions, irregular diffuse border, rough texture, pain on the vermilion of both lips, and fissured lesions, irregular, with bleeding, on the commissure of labium extra. The clinical appearance was characterized as erythema multiforme and treated with triamcinolone acetonide, which gave a good response.Discussion: Reactions to paracetamol may be due to the paracetamol-specific IgE or T cells. Some cases have been reported of hypersensitivity to paracetamol, which causes similar symptoms and can be more severe, like Steven Johnson Syndrome (SJS). An allergy panel is needed to determine the exact hypersensitivity experienced by the patient to support recovery and prevent recurrence.Conclusion: Cases of Erythema multiforme due to paracetamol ingestion are rare. However, it is important to remember that adverse drug reactions may occur in certain individuals. Clinicians should be aware of such occurrences to take appropriate action.Keywords: Erythema Multiforme, Hypersensitivity, Paracetamol, Triamcinolone Acetonide